THE METHOD OF DETERMINATION OF ERROR IN THE REFERENCE VALUE OF THE DOSE DURING THE LINEAR ACCELERATOR RADIATION OUTPUT CALIBRATION PROCEDURE. Part 3. The dependence of the radiation beam characteristics - E. V. Titovich; I. G. Tarutin; M. G. Kiselev (Приборы и методы измерений)
To ensure the radiation protection of oncology patients is needed to provide the constancy of functional characteristics of the medical linear accelerators, which affect the accuracy of dose delivery. For this purpose, their quality control procedures are realized including calibration of radiation output of the linac, so the error in determining the dose reference value during this procedure must not exceed 2 %. The aim is to develop a methodology for determining the error in determining this value, depending on the characteristics of the radiation beam. Dosimetric measurements of Trilogy S/N 3567 linac dose distributions have been carried out for achievement of the objectives, on the basis of which dose errors depending on the dose rate value, the accuracy of the beam quality and output factors determination, the symmetry and uniformity of the radiation field, the angular dependence of the linac radiation output were obtained. It was found that the greatest impact on the value of the error has the error in the output factors determination (up to 5.26 % for both photon energy). Dose errors caused by changing dose rate during treatment were different for two photon energies, and reached 1.6 % for 6 MeV and 1.4 % for 18 MeV. Dose errors caused by inaccuracies of the beam quality determination were different for two photon energies, and reached 1.1 % for 18 MeV and –0.3 % for 6 MeV. Errors caused by the remaining of the characteristic do not exceed 1 %. Thus, there is a possibility to express the results of periodic quality control of the linear accelerator in terms of dose and use them to conduct a comprehensive assessment of the possibility of clinical use of a linear accelerator for oncology patients irradiation on the basis of the calibration of radiation output.